Penerapan Penilaian Portofolio untuk Meningkatkan Karakter Mandiri Siswa dalam Pembelajaran IPS Kelas VIII MTs Negeri 1 Sragen - Sri Lestari; Sudarmiani; Yudi Hartono (Institut Agama Islam Negeri Ponorogo, 2025)
The teaching methods and assignment variations are crucial in enhancing student learning outcomes and character development. This research seeks to improve students' academic performance and character development by applying an independent character-building learning approach. A classroom action research design was adopted over two cycles between January and April 2025. Data were gathered through observation and testing, and subsequently analyzed using qualitative and quantitative methods. The research results indicate that student learning outcomes and character in Class VIII E at MTs Negeri 1 Sragen can be improved through learning using the portfolio assessment method. Learning outcomes improved, as evidenced by the average score rising from 72.41 in Cycle I to 93.10 in Cycle II. Meanwhile, the improvement in character is shown by a